Cultural intelligence and expatriate performance in global assignment: the mediating role of adjustment - Sri Ramalu, Subramaniam; Che Rose, Raduan; Uli, Jegak; Samy, Naresh Kumar (Universiti Malaysia Sarawak, 2012)
This paper investigates the relationship between cultural intelligence and job performance, and the mediating role of cross-cultural adjustment in that relationship. Based on sample of 332 expatriates working in Malaysia, cultural intelligence predicts job performance, and both the interaction and work adjustment mediates the relationship. The findings of this study contributes to the body of knowledge in the cross-cultural management field as well as practical implication to expatriating firms especially in the area of selection and training of international candidates.